PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN APPYPIE PADA MATERI PERSAMAAN TRIGONOMETRI - FITRI HIDAYATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The Covid-19 phenomenon has increased the awareness of educators to be able to take advantage of learning media that uses communication information technology so that learning continues well. One of learning media that is easy to make is android-based learning media using appypie. By using appypie, teachers easily create their own learning applications/media that contain content according to the learning objectives to be achieved without having to have knowledge of coding or programming. The purpose of this research is to produce android-based learning media using appypie which can be used as an alternative valid and effective learning media for students. This type of study is research and development (R&D) using the ADDIE model. The ADDIE model consists of five stages, 1) Analysis; 2) Design; 3) Development; 4) Implementation and 5) Evaluation. The Research instruments is questionnaire, which are used to obtain data on the level of worthiness (validity). The results of the validation by media experts obtained an average of 80.40% which is included in the